Analysis of the state of sustainable development and key targets: A case study of China and “Belt and Road” countries - Shun Chen; Ping Jiang; Pin Zuo; Zolboo Dashnyam (Heliyon)
This study examines the sustainable development progress of China, Kazakhstan, Mongolia, and Pakistan under the Belt and Road Initiative (BRI) from 2000 to 2019, using 63 indicators across 17 Sustainable Development Goals (SDGs). These countries were selected due to their significant energy reserves and their pivotal role in the BRI's green sustainable development goals. As major energy producers in China's vicinity, their cooperation in environmental governance and carbon neutrality offers a tremendous opportunity to align their sustainability efforts, directly contributing to both regional and global SDG targets. By applying data from the Sustainable Development Solutions Network (SDSN) and Bertelsmann Stiftung, and utilizing social network analysis and principal component analysis, the study identifies key SDGs and explores their interlinkages across these countries. The findings underscore the critical need for these nations to focus on environmental and social sustainability, fostering enhanced cooperation in green development. This research provides valuable insights for policymakers to formulate effective, data-driven green policies, promoting long-term sustainable development and cooperation within the BRI framework.